Immunological and physicochemical properties of cervical ovulatory mucus - Ulcova-Gallova, Z (Journal of reproductive immunology, 2010)
Selected biochemical and immunological parameters of cervical ovulatory mucus collected at ovulation have been determined. These include the levels of glucose, fructose, immunoglobulins, C3, hormones, prostaglandin E2, Th1 and Th2 cytokines and antibodies to sperm (and the local effect of hydrocortisone treatment on their levels), zona pellucida, phospolipids and laminin-1. The results of these studies are relevant to the problems associated with fertility disorders and repeated loss of pregnancy.
Keywords: laminin; Glucose; glukosa; fruktosa; ovulace; Immunoglobulins; těhotenství; ženská infertilita; cytokiny; Adult; Cytokines; Fructose; Ovulation; Cervix Mucus; Infertility, Female; cervikální hlen; ženské pohlaví; Humans; Laminin; Phospholipids; Pregnancy; Dinoprostone; imunoglobuliny; dospělí; Female; fosfolipidy; dinoproston; lidé